EFEK SUMBER KARBON PADA PROPERTI LUMINESENSI BCNO YANG DISINTESIS DENGAN METODE PEMANASAN GELOMBANG MIKRO - Feri Ramdani; Irfana Diah Faryuni; Abdul Muid; Joko Sampurno; Bebeh Wahid Nuryadin; Fatimah Arofiati Noor (Jurnal Fisika FLUX, 2016)
ABSTRACT- A BCNO phosphor was successfully synthesized using a microwave method and atmospheric pressure. The phosphors were prepared from precursors containing boric acid as a boron source, urea as a nitrogen source and poly ethylene glycol (PEG) as a carbon source. The carbon sources were varied by PEG MW 1000, MW 6000 and MW 20000.  The objective of this research is to study the effect of variations in the carbon source to the luminescence properties of BCNO that synthesized using microwave. The emission wavelength of the samples are in violet area (380-450 nm) and the highest emission intensity was 47 a.u. produced by BCNO which using PEG MW 20000 as the carbon source.